3D kirigami metamaterials with coded thermal expansion properties. (October 2020) - Yang, Nan; Zhang, Mingkai; Zhu, Rui
Abstract: Capability of achieving desired thermal expansions is critically important for various engineering applications. Inspired by the morphable kirigami patterns, three-dimensional (3D) mechanical metamaterials are designed and fabricated with their effective thermal expansion properties being coded within the fundamental thermo-mechanical coupled microstructures. With the concept of 'bit' being introduced in the basic quarter unit, we construct ring-like unit cells which are assembled to form different 2D and 3D metamaterials with programmable elastic deformations upon changes in temperature. Both simulations and experiments are performed at different levels of the architectured materials indicating that the targeted isotropic and anisotropic deformations can be achieved in a large range (from -40% to 10% strain). Finally, the positively correlated relation between thermal expansion property and Poisson's ratio is also discussed. This work opens up new avenues for potential mechanical metamaterial applications in deformable electronics, self-folding materials, artificial muscles, and robotics.